One-pot construction of Quenchbodies using antibody-binding proteins. Issue 43 (24th October 2016) - Jeong, Hee-Jin; Kojima, Tomoki; Dong, Jinhua; Ohashi, Hiroyuki; Ueda, Hiroshi
Abstract : A novel method to construct a fluorescent biosensor Quenchbody in one pot is devised using an optimized fluorescence-labeled antibody binding protein and human/mouse antibody Fab fragment. Abstract : Fluorolabeled antibody-binding proteins were constructed based on Staphylococcus protein A and Streptococcus protein G domains, and used as an adaptor to convert the Fab fragment of interest to a Q-body, a fluorescent biosensor that exhibits antigen-dependent fluorescence enhancement. Without having to perform the tedious procedure of genetically introducing a fluorescent dye molecule into a cloned Fab fragment, we successfully converted both a cloned anti-osteocalcin Fab fragment and a commercially available anti-vimentin (Fab)2 fragment to a Q-body using this method. This method is not only a simpler way for constructing Q-bodies but also a convenient alternative to finding a suitable antibody that has a greater potential to become an excellent biosensor.